Pelvic artery embolization versus vaginal packing for controlling vaginal bleeding in locally advanced cervical cancer: a retrospective cohort study from a tertiary cancer center in Xinjiang, China - Yang, Hong; Xu, Fenglin; Liu, Yuhan; Chen, Qiuyu; Song, Yonghui; Wu, Yu; Zhong, Wei; Xiong, Tingchuan; You, Lina; Huang, Wukui (Frontiers in Oncology, 2026)
IntroductionVaginal bleeding is a frequent and potentially life-threatening complication in locally advanced cervical cancer. Pelvic artery embolization (PAE) directly occludes the bleeding arteries and allows targeted hemostasis, whereas vaginal packing (VP) relies on temporary mechanical compression. Theoretically, PAE may achieve faster and more durable bleeding control. However, few studies have compared the efficacy and safety of these two methods, limiting the early application of PAE. This study aimed to compare the effectiveness and safety of PAE versus VP, and to identify factors influencing hemostatic efficacy.MethodsThis retrospective cohort study was conducted at a single tertiary cancer center in Xinjiang, China, and included patients with locally advanced cervical cancer presenting with vaginal bleeding between January 2010 and December 2024. Patients were categorized into the VP group (135 cases) and the PAE group (150 cases) based on the hemostatic intervention received. Next, we compared the hemostatic efficacy, adverse reactions, and recurrence of bleeding between the two groups. Multivariate logistic regression analysis was subsequently employed for identify the factors influencing hemostatic efficacy.ResultsA total of 285 patients were included in this study. Compared with the VP group, the PAE group achieved significantly higher overall hemostatic efficacy (94.0% vs. 57.8%, P<0.001) and a lower recurrence rate of bleeding (3.3% vs. 10.4%, P=0.017). Regarding adverse reactions, the incidence of fever was higher in the PAE group (15.3% vs. 6.7%, P=0.021), whereas local infection and pelvic persistent pain were less frequent (2.7% vs. 12.6%, P=0.001; 30.7% vs. 46.7%, P=0.006). Multivariate analysis indicated that FIGO stage ≥ IIIA was independently associated with reduced hemostatic efficacy (OR=0.333, 95% CI=0.157-0.708, P=0.004), while PAE was independently associated with improved hemostatic efficacy (OR=14.026, 95% CI=6.343-31.015, P<0.001).ConclusionPAE is more effective than VP in controlling vaginal bleeding in locally advanced cervical cancer and may be considered as an early therapeutic option when feasible. FIGO stage ≥ IIIA is identified as a risk factor for effective hemostasis, whereas PAE serves as a strong protective factor.